The Effect of the Conceptual Change Model on Conceptual Understanding of Electrostatics - Johannes Addido; Andrea Burrows; Timothy Slater (Education Sciences, 2022)
This research investigated the effectiveness of the conceptual change model (CCM) in addressing pre-service elementary teachers’ misconceptions and promoting their conceptual understanding of electrostatics. The participants were 55 pre-service elementary teachers enrolled in an elementary physical science course, 44 females and 11 males. An embedded mixed-methods approach was employed to help answer the two research questions put forward in this research. The results showed that the CCM moderately correlated with participants’ conceptual understanding of electrostatics. The data from the three open-ended questions showed that the CCM positively affected participants’ conceptions of the topic of electrostatics. The results of this research contribute to the literature on the effect of the conceptual change model in building conceptual understanding and minimizing pre-service teachers’ misconceptions about electrostatics. The results also showed that the phases of the CCM did not have the same effect on participants’ conceptual understanding of electrostatics. This information brings to the fore a discussion about the optimal approach to using the conceptual change instructional model.